A case of atypical Kabuki syndrome arising from a novel missense variant in HNRNPK. Issue 5 (3rd August 2017) - Miyake, N.; Inaba, M.; Mizuno, S.; Shiina, M.; Imagawa, E.; Miyatake, S.; Nakashima, M.; Mizuguchi, T.; Takata, A.; Ogata, K.; Matsumoto, N.
Abstract : A novel causative variant (c. 464T>C, p.Leu155Pro) in the heterogeneous nuclear ribonucleoprotein K ( HNRNPK ) gene.